2018
DOI: 10.34001/jdc.v2i2.705
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Pendapatan Rumah Tangga Melalui Pemberdayaan Ibu-Ibu PKK

Abstract: The aim of this dedication is to train the PKK member to make accessories and increase their family income. The partner of this dedication is RT 01 RW 07 in Mlati Norowoti Village, Kudus Regency, especially the PKK group. The methods using in this service are entrepreneurship counseling and training in making hijab handmade accessories. PKK Group was delighthened with this program. They can practice making the accessories from acrylic based. The result of this dedication to the people activity was the PKK grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…The efforts for eliminating poverty should be directed to the basic food necessity fulfillment considering the food intake "the filling of my plate." (Alifiana, 2018;Karwati, 2017) revealed that the society prosperity enhancement by income enhancement needs to conduct by microeconomic strategies such as the entrepreneurship ecosystem establishment based on conducive local resources. According to this scheme, the number of tourists does not just increase, but also the entrepreneur capability quality.…”
Section: Discussionmentioning
confidence: 99%
“…The efforts for eliminating poverty should be directed to the basic food necessity fulfillment considering the food intake "the filling of my plate." (Alifiana, 2018;Karwati, 2017) revealed that the society prosperity enhancement by income enhancement needs to conduct by microeconomic strategies such as the entrepreneurship ecosystem establishment based on conducive local resources. According to this scheme, the number of tourists does not just increase, but also the entrepreneur capability quality.…”
Section: Discussionmentioning
confidence: 99%
“…3. Pendampingan dengan diskusi bersama atas mitigasi risiko aspek pemasaran dan SDM Aspek Pemasaran; Pelatihan pemasaran yang lebih memadai adalah melalui pengenalan e-commerce atau market place dan social media sebagai salah satu sarana pemasaran (Alifiana, 2018). Strategi pemasaran digital yang optimal dapat membentuk model bisnis berkelanjutan dari produk minuman kopi disaat pandemic Covid-19 (Adithia & Jaya, 2021).…”
Section: Gambar 3 Pelatihan Pembuatan Media Social Instagram Dan Goog...unclassified
“…Pemerintah melalui kementerian pemberdayaan perempuan dan perlindungan anak (KPPPA) sejak tahun 2012 telah menjalankan program peningkatan produktivitas ekonomi perempuan (PPEP) untuk peningkatan kualitas hidup dan pemenuhan hak ekonomi perempuan melalui penguatan produktivitas ekonomi perempuan (Alifiana, 2018;VH & Susilowati, 2016). Kegiatan yang dilakukan antara lain dengan memberikan perhatian khusus kepada kelompok keluarga yang belum dapat memenuhi kebutuhan dasarnya.…”
Section: Pendahuluanunclassified